Implementation of Deep Back Massage in Maternity Period 1 - Krismiyati, Murti; Setianingsih, Indriah Budi; Mahmudah, Siti (Global Health Science Group, 2024)
Childbirth is the process by which the baby, placenta and amniotic membrane come out of the mother's uterus. Pain in labor is uterine contraction pain that can result in increased activity of the sympathetic nervous system. Deep back massage is an emphasis on the sacrum that can reduce tension in the sacolacyous joint from the posterior occiput position of the fetus. Objective: This study aims to determine the effect of deep back massage on labor pain in phase I. Method: This type of research is qualitative with a case study research method using the Continuity Of Care (COC) midwifery care approach. Deep back massage pain management is carried out during phase I. Then the evaluation is carried out every 30 minutes by assessing the pain scale using a pretest-posttest design using the Wong-Baker FACES Pain Rating Scale (facial scale) and Comparative Pain Scale techniques. Results: Pain in labor in the first period decreases after a deep back massage. Conclusions: The implementation of deep back massage can reduce pain in mothers who give birth in the first trimester.